Rise of Intellectual Workers and Intellectual Work - Maria Jakubik (International Journal of Management, Knowledge and Learning, 2020)
This paper seeks to answer the questions What is human intelligence? How does human intellect evolve? How does intellectual worker differ from knowledge worker? How does intellectual work differ from knowledge work? As a synthesis of the literature review, the ‘rise of human intellect’ framework is presented. The novelty of the paper is in proposing to change the ‘knowledge worker’ and ‘knowledge work’ concepts introduced by Peter Drucker in the 1950s to ‘intellectual worker’ and ‘intellectual work’ because they seem to be more appropriate terms with the move from the knowledge economy to the creative and mind economy.